2020
DOI: 10.1002/wat2.1467
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for cold‐regions groundwater numerical modeling

Abstract: The impacts of ongoing climate warming on cold-regions hydrogeology and groundwater resources have created a need to develop groundwater models adapted to these environments. Although permafrost is considered relatively impermeable to groundwater flow, permafrost thaw may result in potential increases in surface water infiltration, groundwater recharge, and hydrogeologic connectivity that can impact northern water resources. To account for these feedbacks, groundwater models that include the dynamic effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 176 publications
1
32
0
Order By: Relevance
“…A similar LUT approach was utilized for case 2, and similar meteorological conditions were determined only by R g within a time window of 7 d. For case 3, the missing value of NEE was replaced by the average value of adjacent hours (within 1 h) on the same day or at the same time of the day, which was derived from the mean diurnal course within 2 d. The aforementioned three steps were repeated with increased window sizes until the missing value could be properly filled. Finally, NEE was separated into GPP and R eco by nighttime-based and daytime-based approaches (Lasslop et al, 2010). Land surface energy fluxes (LE, H ) were processed simultaneously using the aforementioned u * filtering and gap filling methods with the REddyProc package.…”
Section: Land Surface Energy and Carbon Fluxes And Vegetation Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar LUT approach was utilized for case 2, and similar meteorological conditions were determined only by R g within a time window of 7 d. For case 3, the missing value of NEE was replaced by the average value of adjacent hours (within 1 h) on the same day or at the same time of the day, which was derived from the mean diurnal course within 2 d. The aforementioned three steps were repeated with increased window sizes until the missing value could be properly filled. Finally, NEE was separated into GPP and R eco by nighttime-based and daytime-based approaches (Lasslop et al, 2010). Land surface energy fluxes (LE, H ) were processed simultaneously using the aforementioned u * filtering and gap filling methods with the REddyProc package.…”
Section: Land Surface Energy and Carbon Fluxes And Vegetation Dynamicsmentioning
confidence: 99%
“…In this regard, researchers have stressed the necessity to simultaneously couple the water and heat transfer process in dry/cold seasons (Scanlon and Milly, 1994;Bittelli et al, 2008;Zeng et al, 2009a, b;Jiang et al, 2012;Yu et al, 2016Yu et al, , 2018. Concurrently, researchers developed dedicated models, e.g., SHAW (Flerchinger and Saxton, 1989), HYDRUS (Hansson et al, 2004), MarsFlo (Painter, 2011), its successor Advanced Terrestrial Simulator (Painter et al, 2016), and Simultaneous Transfer of Energy, Mass and Momentum in Unsaturated Soil with Freezing and Thawing (STEMMUS-FT) (Yu et al, 2018(Yu et al, , 2020, implementing the soil water and heat coupling physics for frozen soils (see reviews of the relevant models in Kurylyk and Watanabe, 2013;Grenier et al, 2018;Lamontagne-Hallé et al, 2020). Promising simulation results have been reported for the soil hydrothermal regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Soil moisture memory was shown by Cosgrove et al (2003) and Rodell et al (2005) to be larger than thermal memory for shallow soil columns (2m and 3.5m), such that reaching a quasi-equilibrium state for moisture during spin-up requires more time than soil temperature, depending on soil characteristics. However, such conclusions may not be valid for deeper soil columns recommended for LSM simulation of permafrost, due to their larger thermal/hydraulic inertia (Sapriza-Azuri et al , 2018;Elshamy et al , 2020;Lamontagne-Hallé et al , 2020). For example, Elshamy et al (2020) showed that soil moisture stabilized faster than soil temperature in simulations for the Mackenzie River Basin using a 51.24m soil column.…”
Section: Introductionmentioning
confidence: 97%
“…However, gathering extensive datasets over large and remote (e.g. arctic/subarctic) regions and significant depths is challenging (Lamontagne-Hallé et al , 2020). Alternatively, allowing the LSM to generate its own self-consistent initial conditions through a spin-up technique is commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…The use of groundwater flow and transport models to support management efforts is common practice; however, to address the potential for groundwater contamination in cold regions there is a need to adapt solute transport descriptions in mathematical models to account for the presence of pore ice and freezing temperatures (Panday & Corapcioglu, 1994; Vonk et al., 2019). Present solute transport models generally do not consider permafrost dynamics, while cold‐regions groundwater models including solute transport routines are rare (Grenier et al., 2018; Lamontagne‐Hallé et al., 2020). Previous research on subsurface contaminant transport in cold regions has predominantly focused on petroleum spills and active‐layer transport of other non‐aqueous phase liquids (Carlson & Barnes, 2011; Dyke, 2001; Panday & Corapcioglu, 1994).…”
Section: Introductionmentioning
confidence: 99%